ASPEK HUKUM PENGENDALIAN DAN PEMANFAATAN RUANG TERMINAL KHUSUS COASTAL ROAD DALAM RENCANA TATA RUANG WILAYAH KABUPATEN NUNUKAN - Yusi Novianto; Yahya Ahmad Zein (Universitas Borneo Tarakan, 2022)
AbstractIndonesia as an archipelagic country with archipelago characteristics has an official number of islands around 16.056 with a water area of approximately 2/3 of its land area. Having a coastline of 95.181 km makes Indonesia’s coastal areas one of the most productive centers of economic activity. The economic potential should also be supported by the management of the coastal environment which has the potential to be damaged and polluted in coastal areas. Nunukan Regency, North Kalimantan Province, since its formation in 1999 has had a Regional Spational Plan in the form of Perda Number 19 of 2013 concerning Regional Spatial Planning for 2013 - 2033. Perda number 19 of 2013 contains a process system for spatial planning, spatial use, and spatial use control as an elaboration of Law Number 26 of 2007 concerning Spatial Planning and contains management of the coastal area of Nunukan Regency as a representation of the elaboration of Law Number 27 of 2007 concerning Management of Coastal Zone and Small Islands. Based on the report from the DPUPR-PERKIM audit team for North Kalimantan Province, it was found that there were indications of violations in the use of space for the community’s special terminal object (water jetty) on the coastal border of south Nunukan District. This study raises the issue of position and legal implications for the use of special terminal space based on Regional Regulation Number 19 of 2013. Researchers use welfare theory in studying its legal standing. And the implications of legal authority for the existence of special terminal using the legal theory of effectiveness. This type of research is normative legal research with data collection techniques based on legal materials combined with field data. The results of the study found a legal analysis that there was a discrepancy in the use of space for the position of a special terminal along the coastal border. As an implication of the legal position of a special terminal, legislation has provided legal protection and has provided clear and firms limits on prosecution. Spatial Law enforcement is carried out by forming Spatial Planning Civil Servants Investigators (PPNS) as a recommendation from the results of this study.Keywords: Legal Position, authority, local government, PPNS.